Single-Member Company As A Legal Entity And Its Correlation With The Establishment of A Completely Sole-Owned Limited Liability Company Based On Regulation Number 40/2007 Regarding Limited Liability Company In Indonesia - Nicholas Ardyanto; Tjhong Sendrawan (Syntax Literate, 2022)
This Article aims to discuss concerning Single-Member Private Company as a Legal Entity and its Correlation with the establishment of a completely self-owned limited liability company based on the Limited Liability Company Act No. 40/2007 in Indonesia. This study mainly discuss the problem concerning Implication of Legal Entity concept which applied on Single-Member Private Limited Liability Company in Indonesia towards Fully Self-owned Limited Liability company based on Regulation Number 40/2007 regarding Limited Liability Company in Indonesia. This study used the normative-juridical method, where the data used prioritizes library research. The results of the research regarding the problem discussed in this study are that there are several issues related to Single-Member Private Company as a Legal Entity and its Correlation with the Establishment of a Completely Self-owned Limited Liability Company based on Regulation Number 40/2007. First, Indonesia Regulation Number 40/2007 adopts the principle of Limited Liability Company must be established based on an agreement by more than one person, however with regard to the concept of an Individual Company as a Legal Entity and through the implementation of Government Regulation 8/2021, the establishment of a Completely Sole-owned Limited Liability Company is fully possible, either directly in the case of a Single-Member Private Company on a Micro and Small Business scale (MSEs), or indirectly on a Medium and Large Business Scale (Non-MSEs), where the Completely Single-Owned Limited Liability Company is carried out by the Establishment by a Single-Member Private Company together with the Founder of the Single-Member Private Company itself. Second, regarding the effectiveness of the Government Regulation 8/2021 especially article 9 paragraph 1b which limits Single-Member Private companies to only micro and small enterprises (MSEs). These problems occur due to the absence of prohibitions on the use of single-member private companies in the Establishment of Limited Liability Companies in Indonesia, and also because of the principle of Limited Liability Companies must be established based on agreements itself. With the application of the concept of an Individual Company as a Legal Entity in Indonesia, the Possibility of Completely Single Incorporator / Completely single-owned on Limited Liability Companies in Indonesia is fully opened. Both, whether its Micro and Small Business (MSEs) scale or Medium and Large Business (Non-MSEs). In order to avoid ambiguity, it is better to give a firm regulation regarding the prohibition or the permissibility of the Completely Single-Owned Limited Liability Company in Indonesia.